Long-term effects of tungsten carbide (WC) nanoparticles in pelagic and benthic aquatic ecosystems. Issue 1 (2nd January 2018) - Ekvall, Mikael T.; Hedberg, Jonas; Odnevall Wallinder, Inger; Hansson, Lars-Anders; Cedervall, Tommy
Abstract: As the production and usage of nanomaterials are increasing so are the concerns related to the release of the material into nature. Tungsten carbide (WC) is widely used for its hard metal properties, although its use, in for instance tyre studs, may result in nano-sized particles ending up in nature. Here, we evaluate the potential long-term exposure effects of WC nanoparticles on a pelagic ( Daphnia magna ) and a benthic ( Asellus aquaticus) organism. No long-term effects were observed in the benthic system with respect to population dynamics or ecosystem services. However, long-term exposure of D. magna resulted in increased time to first reproduction and, if the particles were resuspended, strong effects on survival and reproductive output. Hence, the considerable differences in acute vs. long-term exposure studies revealed here emphasize the need for more long-term studies if we are to understand the effects of nanoparticles in natural systems.